(untitled) (African Journal of Biomedical Research, 2020)
Hibiscus asper, a herb used in folklore medicine has demonstrated strong and diverse therapeutic potentials, such as, anti-inflammatory, anti-oxidant, anti-depressant, and widely used in the management of diseases. Despite the ethno-pharmacological value of this plant, no study has been conducted to evaluate its anti-ulcerogenic activity. Methanol fraction of Hibiscus asper leaves (100, 200 and 400 mg/kg) was used to investigate anti-ulcerogenic activity in acidified ethanol-induced ulceration model, whereas, Omeprazole was used as the standard drug; both were administered orally. Pre-treatment of rats with the plant fraction significantly inhibited development of gastric ulcers by oral administration of acidified-ethanol in a dose-dependent manner, presenting protection to ulceration of 46.6 % to 81 % as doses increased from 100 to 400 mg/kg. No significant difference was observed in gastric protection presented by Omeprazole pre-treated control group (87.6 %) and the fraction, at doses of 200 (76.3 %) and 400 mg/kg (81 %). More so, histological examination performed revealed that the gastric mucosa of rats pre-treated with fraction, exhibited reduced gastric lesions and sub-mucosal oedema relative to the positive control, which comparatively showed gastric mucosal protection. Therefore, the study suggests that Hibiscus asper might possess some protective and healing potentials in rats which might be due to the stimulation of prostaglandin synthesis